Phospholipase A2 from hymenopteran venoms: Biochemical characterization - Palma, Mario Sergio [UNESP] (1997)
Instituto de Biociencias Departamento de Biologia UNESP, Rio Claro, Avenida 24-A, 1515 Bela Vista, CEP 13500-900, Rio Claro, SP